Effect of temperature on the biology and thermal requirements of Pseudaletia sequax (Lop.: Noctuidae), on artificial diet. - Salvadori, José Roberto; Parra, José Roberto Postali (Pesquisa Agropecuaria Brasileira, 2014)
The effect of six temperatures (18, 20, 22, 26, 30 e 32ºC) on the biology of immature stages of Pseudaletia sequax Franclemont, 1951 (Lep.: Noctuidae), was studied in laboratory, on artificial diet. The adult parameters were also evaluated at 25 ± 2ºC and 28 ± 2ºC. The viability and the length of embrionary, larval and pupal stages, and the pupal weight was affected by the temperature. The length of development decreased with the increase of temperature of 2010 30ºC for the eggs, and 18 to 30ºC for larvae and pupae. As for the adults, the temperature affected the longevity, the preoviposition and oviposition periods as well as the capacity of laying eggs; the thermal condition of 25 ± 2ºC was more suitable than the 28 ± 2ºC one. The values for base temperature (Tb) and K were, respectively, 8,1ºC and 84,4 GD for the egg stage, 8,8ºC and 505,9 GD for the larval stage, 12,5ºC and 180,6 GD for the pupal stage, and 9,1ºC and 804,4 GD during all the period of development. The most adequate thermal condition for rearing this species was found to be between 25 and 26ºC